Predictive factors for acute and late urinary toxicity after permanent interstitial brachytherapy in Japanese patients. (8th January 2013) - Tanimoto, Ryuta; Bekku, Kensuke; Katayama, Norihisa; Kobayashi, Yasuyuki; Ebara, Shin; Araki, Motoo; Takemoto, Mitsuhiro; Yanai, Hiroyuki; Nasu, Yasutomo; Kumon, Hiromi
Abstract : Objectives: To describe the frequency of and to determine predictive factors associated with Radiation Therapy Oncology Group urinary toxicity in prostate brachytherapy patients. Methods: From January 2004 to April 2011, 466 consecutive Japanese patients underwent permanent iodine‐125‐seed brachytherapy (median follow up 48 months). International Prostate Symptom Score and Radiation Therapy Oncology Group toxicity data were prospectively collected. Prostate volume, International Prostate Symptom Score before and after brachytherapy, and postimplant analysis were examined for an association with urinary toxicity, defined as Radiation Therapy Oncology Group urinary toxicity of Grade 1 or higher. Logistic regression analysis was used to examine the factors associated with urinary toxicity. Results: The rate of Radiation Therapy Oncology Group urinary toxicity grade 1 or higher at 1, 6, 12, 24, 36 and 48 months was 67%, 40%, 21%, 31%, 27% and 28%, respectively. Grade 2 or higher urinary toxicity was less than 1% at each time‐point. International Prostate Symptom Score was highest at 3 months and returned to normal 12 months after brachytherapy. On univariate analysis, patients with a larger prostate size, greater baseline International Prostate Symptom Score, higher prostate V100, higher prostate V150, higher prostate D90 and a greater number of seeds had more acute urinary toxicities at 1 month and 12 months after brachytherapy. On multivariate analysis, significant predictors for urinary toxicity at 1 month and 12 months were a greater baseline International Prostate Symptom Score and prostate V100. Conclusions: Most urinary symptoms are tolerated and resolved within 12 months after prostate brachytherapy. Acute and late urinary toxicity after brachytherapy is strongly related to the baseline International Prostate Symptom Score and prostate V100.